Functional autonomy of elderly women enrolled in a physical activity program - doi 10.4025/actascihealthsci.v34i2.8387 - Fernanda de Noronha Ribeiro Daniel; Rodrigo Gomes de Souza Vale; Tânia Santos Giani; Silvia Bacellar; Estélio Herinque Martin Dantas (Universidade Estadual de Maringá, 2012)
The present study aimed to determine the effects of a physical activity program on the functional autonomy of elderly women. The sample was divided into an experimental group (EG; n = 20; 68.51 ± 5.02 years; BMI = 27.01 ± 4.35) submitted to a physical activity program, and a control group (CG; n = 20; 67.01 ± 3.51 years; BMI = 26.71 ± 5.74). Functional autonomy was assessed using tests from the GDLAM autonomy protocol: 10 meter walk test (10MW), rising from a sitting position (RSP), rising from a ventral decubitus position (RVDP), rising from a chair and moving around the house (RCMH) and putting on and taking off a t-shirt (PTT), after which the autonomy index (AI) was calculated. In the EG, ANOVA showed significant reductions in execution times for the RSP (∆ = -3.92 s; p = 0.0001), RCMH (∆ = -9.61 s; p = 0.0001), 10MW (∆ = -0.94 s; p = 0.038) and RVDP (∆ = -1.15 s; p = 0.036) tests, as well as the AI (∆ = -6.27; p = 0.0001). This was not observed in the CG. Intergroup comparisons demonstrated that execution times for the RSP (∆% = -36.63; p = 0.0001), RCMH (∆% = -20.27; p = 0.0001), 10mW (∆% = -12.54; p = 0.002) and RVDP (∆% = -25.10; p = 0.005) tests and the AI (∆% = -21.37; p = 0.0001) of the EG were shorter than those of the CG. These results indicate that elderly subjects in the EG showed improved performance in activities of daily living after engaging in physical exercise.